Gratitude, Self-Control, and Self-Acceptance among Women Victims of Domestic Violence - Valenciarani, Evelina Mei Ling; Noviekayati, IGAA; Santi, Dyan Evita (Kirana Publisher (KNPub), 2025)
This study aims to understand the relationship between gratitude and self-control with self-acceptance in women who experience domestic violence (DV). Gratitude is defined as an individual’s acknowledgment of the presence of others or certain sources that play a role in providing the blessings they receive. Meanwhile, self-control refers to an individual’s ability to direct, regulate, and manage their behavior as well as control negative impulses that arise within themselves. Self-acceptance, on the other hand, is a positive attitude toward oneself, in which individuals are able and willing to accept their condition, including both strengths and weaknesses. The method used in this study employed a quantitative correlational approach, involving 349 women who were victims of domestic violence. The results of the first hypothesis test showed f = 12.233 and p = 0.000 (p < 0.05), indicating a significant relationship between gratitude and self-control with self-acceptance in women experiencing domestic violence. The second hypothesis test revealed a significant positive relationship between gratitude and self-acceptance, with a Pearson correlation value of 0.190 and p = 0.000 (p < 0.05). This means that the higher the level of gratitude, the higher the self-acceptance among women victims of domestic violence. The third hypothesis test showed a significant positive correlation between self-control and self-acceptance, with a Pearson correlation value of 0.184 and p = 0.004 (p < 0.05). This suggests that the higher the level of self-control, the higher the self-acceptance among women victims of domestic violence. Gratitude and self-control contributed an effective variance of 6.6% to self-acceptance.